Efecto de las condiciones de prensado en el rendimiento y calidad del aceite de las semillas de piñón blanco (Jatropha curcas L.), en la estación experimental agraria el porvenir distrito de Juan Guerra – Región San Martín - Ñique Mesia, Thais Evita (2016)
In this research the highest performance and best quality oil obtained was evaluated. The conditions to which underwent treatments helped consolidate a preheat temperatura and rotation speed of the press to help us get higher yields in the press, likewise meet oil quality and that it is within the range of technical standards for the production of biodiesel. Tests were performed with two ecotypes representad by Totorillayco and Yoro three preheat temperaturas seeds white pinion (50º C, 70º C, 90º C) and three rotational speeds of the press (20, 24, and 28 rpm). The best treatments were obtained at higher temperaturas preheat seeds, quality analysis values did not show much difference between the ecotypes, being the results within the quality standards of oil for biodiesel. In one Proximate analysis Lipid 31.67% to 32.40% for Totorillayco and Yoro, which also indicates a higher yield in lipid extraction solvent was obtained. Similarly there was no significant difference in total much ash, 4.44% and 4.02% for Totorillayco for Yoro, crude fiber 30.98% and 30.09% for Totorillayco for Yoro and 27.81 % crude protein for one Totorillayco and 26.62% for Yoro. Physico-chemical analysis determinad the nut oil white based on the average reportad: acid number, 1.29 mg KOH/g oil, iodine, 100.64 g iodine/100 g oil, peroxide, 5.86 mg 02/kg oil , saponification, 193.12 mg KOH/g oil, density 0.930 g/cm3 and viscosity, 50.92 mm2/s, which indicate that these values are within acceptable quality parameters of oil for biodiesel production. The best performance was with oil T17 representing Yoro treatment at 90 º C and 24 rpm with a 26.66%.